Improving nutrient values of palm kernel cake (PKC) by reducing shell contamination and enzymes supplementation - AP, Sinurat; T, Purwadaria; T, Pasaribu (Indonesian Animal Sciences Society, 2013)
Inclusion of palm kernel cake (PKC) in poultry feed is limited due to shell contamination and its low nutritive values, despite the increase of PKC production. Therefore, a series of experiment was conducted in order to improve nutritive values of palm kernel cake (PKC) by sieving and enzyme supplementation. First experiment was designed to reduce shell content using shiever with different diameters (1, 2 and 4 mm). Shell content was measured manually to determine the effect of the sieving. The second experiment was carried out by blowing the after sieving at 2 mm shieve PKC, to produced heavy, medium and light fractions. The shell content and nutrient contents of the medium and light fractions were compared to those of unsieved PKC. In the third experiment, the sieved PKC was supplemented with 2 enzymes with different concentrations, i.e., BS4 at 10, 15 and 20 ml/kg PKC and a commercial multi enzymes at 0.5, 1.0 and 2.0 g/kg PKC. Digestibility of nutrients (dry matter, crude protein and TME) were measured by force feeding method with six replications for each sample. Results of the study showed that sieving with 2 mm diameter siever without blowing was effective in reducingÂ about 50% of PKC shell and improved crude protein, ether extract and amino acids, contents and reduced the crude fiber content of the PKC. Supplementation of enzymes improved the digestibility of dry matter, crude protein and the true metabolisable energy (TME) of the PKC. Optimum improvement was obtained when PKC was supplemented with 20 ml BS4 enzymes/kg PKC. Similar improvement was obtained by supplementation of commercial multi enzymes at 2 g/kg PKC. Therefore, in order to improve the nutritive values of PKC, it is suggestedÂ to sieve the PKC followed by supplementation of enzyme prior to feeding. Key Words: Palm Kernel Cake, Sieve, Enzymes, Nutritive Values.